2018
DOI: 10.1136/openhrt-2018-000889
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiovascular drugs attenuated myocardial resistance against ischaemia-induced and reperfusion-induced injury in a rat model of repetitive occlusion

Abstract: ObjectiveWe investigated the impact of cardioprotective drugs on ST-elevation, arrhythmias and infarct size in a rat model of repetitive coronary artery occlusion.MethodsSeventy Sprague-Dawley rats were randomised to two control and five treatment groups. Placebo was either implantation of a pneumatic occluder onto the left anterior descending coronary artery (LAD) without starting repetitive occlusion (SHAM) or subsequent RO of the LAD over 10 days without medication (ROP). Treatment groups underwent RO and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Thus, the preservation of cell membrane integrity includes maintenance of Ca 2+ homeostasis, various types of ion exchange receptormediated mechanisms, osmotic control, and the preservation of the rich-energy phosphates. Therefore, interventions, e.g., Ca 2+ channel antagonists (Tosaki et al, 1987a;Otani et al, 2013;Becerra et al, 2016), beta-adrenergic receptor blockers (Tosaki et al, 1987b;Winchester and Pepine, 2014;Gatzke et al, 2018), and several other newly discovered molecular structures and interventions (Wilder et al, 2016;Bukhari et al, 2018;Gatzke et al, 2018), which directly or indirectly contribute to the preservation of the aforementioned processes can diminish the incidence of reperfusion-induced arrhythmias, heart failure, and sudden cardiac death. In addition, during the past three decades several new mechanisms have been proved and implicated based on molecular biological studies, as endogenous mediators, into the pathways of ischemia/reperfusion-induced injury and arrhythmogenesis, including gaseous molecules; nitric monoxide, carbon dioxide, and hydrogen sulfide.…”
Section: Ca 2+mentioning
confidence: 99%
“…Thus, the preservation of cell membrane integrity includes maintenance of Ca 2+ homeostasis, various types of ion exchange receptormediated mechanisms, osmotic control, and the preservation of the rich-energy phosphates. Therefore, interventions, e.g., Ca 2+ channel antagonists (Tosaki et al, 1987a;Otani et al, 2013;Becerra et al, 2016), beta-adrenergic receptor blockers (Tosaki et al, 1987b;Winchester and Pepine, 2014;Gatzke et al, 2018), and several other newly discovered molecular structures and interventions (Wilder et al, 2016;Bukhari et al, 2018;Gatzke et al, 2018), which directly or indirectly contribute to the preservation of the aforementioned processes can diminish the incidence of reperfusion-induced arrhythmias, heart failure, and sudden cardiac death. In addition, during the past three decades several new mechanisms have been proved and implicated based on molecular biological studies, as endogenous mediators, into the pathways of ischemia/reperfusion-induced injury and arrhythmogenesis, including gaseous molecules; nitric monoxide, carbon dioxide, and hydrogen sulfide.…”
Section: Ca 2+mentioning
confidence: 99%
“…Furthermore, Wang and his colleagues [44] reported that the administration of NTG decreased ET-1 and CK-MB levels with the resulting prevention of myocardial pathological damage in a rat model of IR injury. Moreover, NTG could activate Na + /K + ATPase pump in the heart and thereby limits Na + and Ca 2+ overload and arrhythmias and decreases the ST segment elevation [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, myocardial stunning (dysfunction) may help to regulate the massive amount of ROS production in myocytes following an I/R injury ( Najafi et al 2018 ). CAT along with the SOD and GPx, play a significant role in the protection against LPO ( Gatzke et al, 2018 , Han et al, 2019 ). According to a recent study, erythrocyte reduction of CAT and SOD in acute myocardial infarction patients is caused by inactivation/alteration of these antioxidant enzymes through cross linking or exhaustion of these antioxidant enzymes through LPO ( Qu et al, 2019 , Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the reperfusion phase of I/R damage, autophagy, apoptosis, and necrosis all cause cell death ( Liu et al 2019 ). Recent years have seen significant enhancements in the protective strategies to suppress all features of post ischemic injury in cardiovascular diseases ( Gatzke et al, 2018 , Liu et al, 2019 ). Due to the scarcity of therapy options, a safer and more effective technique for developing cardiovascular drugs is urgently needed ( Badalzadeh et al, 2014 , Geldi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%